Chemical etching of glasses in hydrofluoric Acid: A brief review. (2022) - Shubhava,; Jayarama, A.; Kannarpady, Ganesh K.; Kale, Sangeeta; Prabhu, Shriganesh; Pinto, Richard
Abstract: The removal of material, selectively or non-selectively, from the surface of glasses by using acidic, caustic, or abrasive chemicals is referred to as glass etching. Wet and dry etchings are extensively used for variety of applications, including flow channel designs in fuel cell electrodes. Since precise micro-level etching is challenging, optimization of the etching parameters is important. This paper reviews wet etching of glasses including fused quartz for formation of microchannels and microstructures for a variety of applications. The review also discusses different etch mechanisms including etch parameters and surface microstructure of the etched glass. It is found that HF concentration and etching time play a major role on the resulting surface microstructure of glass materials. The paper also describes the use of HF buffered with NH4 F solutions to improve the quality of the etched surface.